2015
DOI: 10.1080/08961530.2015.1056328
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the green buying behavior of younger Millennials from India and the United States: A structural equation modeling approach

Abstract: A majority of past studies have used the consumer socialization framework to study children and adolescents in the U.S. but there is a dearth in academic articles that focuses on Millennials. Furthermore, there is a large, understudied Millennial population in India. The purpose of this study was (1) to propose an integrative theoretical model for determining the relative importance of socialization factors on Millennials' green buying behavior and (2) to study the impact of culture in selecting socialization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 75 publications
3
42
0
1
Order By: Relevance
“…Moreover, it is found that social media can improve comparison psychology and self-efficacy and, ultimately, these attributes contribute to promoting pro-environmental behaviors [66][67][68]. It was found that media channels have a direct influence on consumers' attitudes and behaviors toward different kinds of environmental issues such as greenhouse gasses, energy crises and environmental deterioration [69]. Even though digital media is becoming a very popular and impressive tool for direct actions or movements, its success in enacting environmental changes or environmental protection actions or policies is still under investigation [70][71][72].…”
Section: Moderating Role Of Social Mediamentioning
confidence: 99%
“…Moreover, it is found that social media can improve comparison psychology and self-efficacy and, ultimately, these attributes contribute to promoting pro-environmental behaviors [66][67][68]. It was found that media channels have a direct influence on consumers' attitudes and behaviors toward different kinds of environmental issues such as greenhouse gasses, energy crises and environmental deterioration [69]. Even though digital media is becoming a very popular and impressive tool for direct actions or movements, its success in enacting environmental changes or environmental protection actions or policies is still under investigation [70][71][72].…”
Section: Moderating Role Of Social Mediamentioning
confidence: 99%
“…Even if they are more likely to purchase sustainably, other personal factors can take over. Among these, parent-child relationship (Wilcock et al 2004;Jang et al 2011;Lappänen et al 2012;Anvar and Venter 2014;Meeusen 2014;Muralidharan et al 2016;Casaló and Escario 2016;Naderi and Van Steenburg 2018) modifying interest, awareness and therefore the intention to purchase green products (Kanchanapibul et al 2014; Heo and Muralidharan 2017) can be listed.…”
Section: Millennials Consumption and Green Consumption Featuresmentioning
confidence: 99%
“…Age, therefore, does not seem to be a sufficient structural variable to guarantee eco-compatible behaviour (Muralidharan et al 2016). The statistical analysis shows how the influence of ecological knowledge of the younger generations is weaker than personal motivations when it comes to making the purchase decision.…”
Section: Millennials Consumption and Green Consumption Featuresmentioning
confidence: 99%
“…Tang et al (2014) menyelidiki hubungan langsung EC dengan ATGP pada konsumen Tiongkok dan menyarankan bahwa EC adalah faktor kunci yang mempengaruhi sikap konsumen terhadap produk ramah lingkungan. Muralidharan et al (2015) membandingkan preferensi hijau konsumen muda dari India dan Cina. Menurut temuan mereka, EC secara signifikan memengaruhi keputusan pembelian hijau konsumen India dan Cina.…”
Section: Tugas Pengelolaan Bumi Melalui Kepedulian Terhadap Green Conunclassified